2020
DOI: 10.1111/ijn.12888
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the DigniCap System in preventing chemotherapy‐induced alopecia in breast cancer patients is not related to patient characteristics or side effects of the device

Abstract: Background The DigniCap System is an effective scalp cooling device for the prevention of chemotherapy‐induced alopecia in early breast cancer patients. Aim This prospective study was designed to confirm the efficacy and tolerability of the device, to explore potential factors associated with its efficacy and to collect data on patient perceptions and satisfaction. Methods Between January 2016 and June 2018, 163 early breast cancer patients eligible for adjuvant chemotherapy were enrolled. Hair loss was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…scalp cooling system were chills, followed by dizziness and headaches, however most of them were mild. Similar side effects were reported in the literature [15,16]. Regarding quality of life, a recently published systematic review showed that results are still inconsistent [17].…”
Section: Discussionsupporting
confidence: 75%
“…scalp cooling system were chills, followed by dizziness and headaches, however most of them were mild. Similar side effects were reported in the literature [15,16]. Regarding quality of life, a recently published systematic review showed that results are still inconsistent [17].…”
Section: Discussionsupporting
confidence: 75%
“…Our study suggests that hair thickness, structure, density, and manipulation during chemotherapy did not influence the hair preservation rate. In this regard, a series of studies reported that hair thickness, the main hair characteristic investigated, was not a significant factor associated with hair preservation [ 14 , 15 , 16 ], whereas another analysis suggested an inverse association [ 17 ].…”
Section: Discussionmentioning
confidence: 99%